2012
DOI: 10.1007/s00125-012-2503-7
|View full text |Cite
|
Sign up to set email alerts
|

New expectations from the well-known medicinal properties of Arctium lappa

Abstract: AMP-activated protein kinase (AMPK) serves as a major regulator of energy homeostasis and is activated by different glucose-lowering agents. Indeed, AMPK has been identified as an attractive target for the development of innovative molecules to treat type 2 diabetes. In this issue of Diabetologia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
0
6
0
2
Order By: Relevance
“…In fact, glyphosate-based herbicides such as R potently affect the cardiovascular system in mammals [ 42 ]. Arctigenin present in D (in Arctium lappa ) activates muscle uptake of glucose [ 43 ], which could restore the locomotor activity. Berbamine (in Berberis vulgaris ) may modulate myocardial contractility [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, glyphosate-based herbicides such as R potently affect the cardiovascular system in mammals [ 42 ]. Arctigenin present in D (in Arctium lappa ) activates muscle uptake of glucose [ 43 ], which could restore the locomotor activity. Berbamine (in Berberis vulgaris ) may modulate myocardial contractility [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings also need to be investigated further as to explain why there was loss present in subcutaneous fat but not visceral fat as well as no net weight loss despite decrease in subcutaneous fat. Arctigenin holds promise as a potent antidiabetic drug, but all dimensions of arctigenin need to be explored with respect to its beneficial effect on diabetes (Huang et al, 2012;Miele & Beguinot, 2012 Furthermore, Ss showed potent antioxidant ability that helped in counteracting the effects of diabetes and also blocked gluconeogenesis in diabetic mice (Zhao et al, 2017).…”
Section: Articum Lappamentioning
confidence: 99%
“…Synergistisch dazu verbessert das Lignan Arctigenin in an Adipositas leiden den Versuchstieren den Glukose und Fettstoffwechsel. Dabei wird mit der AMPaktivierten Proteinkinase ein attrak tives Zielenzym induziert, das auch ein therapeutisches Target für neue Antidia betika darstellt und eine Verminderung der viszeralen Fettmasse ermöglichen soll (41).…”
Section: Weitere Wirkungenunclassified